PERAN DOSEN PEMBIMBING AKADEMIK DALAM MENINGKATKAN KEDISIPLINAN AKADEMIK MAHASISWA DI UIN SYAHADA - Halimah Sakdiyah; Reza Afrila; Sulham Efendi Hasibuan (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
Academic discipline is an important aspect in the success of students' studies in higher education, which includes attendance at lectures, timely submission of assignments, administrative compliance, and understanding of academic ethics. Academic Advisors (PA) have a strategic role in helping students adjust to these academic demands. This study aims to analyze the role of PA in improving the academic discipline of students at the State Islamic University (UIN) Syekh Ali Hasan Ahmad Addary (Syahada). The study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The research subjects consisted of two PA lecturers, ten students, and two academic staff. The results show that PA carries out five main functions, namely: (1) consultative, through guidance in preparing KRS (Study Plan Plan), selecting courses, and solving academic problems; (2) motivational, in the form of encouragement to increase learning enthusiasm and discipline awareness; (3) monitoring, through monitoring student attendance, grades, and study progress; (4) preventive, by providing direction and early warnings to prevent the emergence of academic problems; and (5) evaluative, through reviewing study results and academic planning each semester. These roles have been proven to help improve student discipline in aspects such as attendance, assignment submission, academic administration, and understanding of academic ethics. However, the implementation of academic advisor guidance still faces several obstacles, such as limited meeting frequency, a high advisor-to-student ratio, and low awareness among some students. This research confirms the crucial role of advisors in fostering student academic discipline, although improvements to the system and guidance intensity are needed to optimize results. ABSTRAK Kedisiplinan akademik merupakan aspek penting dalam keberhasilan studi mahasiswa di perguruan tinggi, yang mencakup kehadiran dalam perkuliahan, ketepatan pengumpulan tugas, kepatuhan administratif, serta pemahaman terhadap etika akademik. Dosen Pembimbing Akademik (PA) memiliki peran strategis dalam membantu mahasiswa menyesuaikan diri dengan tuntutan akademik tersebut. Penelitian ini bertujuan untuk menganalisis peran PA dalam meningkatkan kedisiplinan akademik mahasiswa di Universitas Islam Negeri (UIN) Syekh Ali Hasan Ahmad Addary (Syahada). Penelitian menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan studi dokumentasi. Subjek penelitian terdiri dari dua dosen PA, sepuluh mahasiswa, dan dua staf bagian akademik. Hasil penelitian menunjukkan bahwa PA menjalankan lima fungsi utama, yaitu: (1) konsultatif, melalui bimbingan dalam penyusunan KRS, pemilihan mata kuliah, dan penyelesaian masalah akademik; (2) motivatif, berupa dorongan untuk meningkatkan semangat belajar serta kesadaran disiplin; (3) monitoring, melalui pemantauan presensi, nilai, dan perkembangan studi mahasiswa; (4) preventif, dengan memberikan arahan dan peringatan dini untuk mencegah munculnya masalah akademik; dan (5) evaluatif, melalui peninjauan hasil studi dan perencanaan akademik setiap semester. Peran-peran tersebut terbukti membantu meningkatkan kedisiplinan mahasiswa dalam aspek kehadiran, pengumpulan tugas, ketertiban administrasi akademik, dan pemahaman etika akademik. Namun, pelaksanaan bimbingan PA masih menghadapi beberapa kendala, seperti keterbatasan intensitas pertemuan, rasio PA–mahasiswa yang tinggi, dan rendahnya kesadaran sebagian mahasiswa. Penelitian ini menegaskan bahwa peran PA sangat penting dalam membentuk kedisiplinan akademik mahasiswa, meskipun diperlukan perbaikan sistem dan intensitas bimbingan agar hasilnya lebih optimal.